Using high-resolution laboratory and ground-based solar spectra to assess CH4 absorption coefficient calculations. (March 2017) - Mendonca, J.; Strong, K.; Sung, K.; Devi, V.M.; Toon, G.C.; Wunch, D.; Franklin, J.E.
Abstract: A quadratic-speed-dependent Voigt line shape (qSDV) with line mixing (qSDV+LM), together with spectroscopic line parameters from Devi et al. [1, 2 ] for the 2v3 band of CH4, was used to retrieve total columns of CH4 from atmospheric solar absorption spectra. The qSDV line shape (Tran et al., 2013) [3 ] with line mixing (Lévy et al., 1992) [4 ] was implemented into the forward model of GFIT (the retrieval algorithm that is at the heart of the GGG software (Wunch et al., 2015) [5 ]) to calculate CH4 absorption coefficients. High-resolution laboratory spectra of CH4 were used to assess absorption coefficients calculated using a Voigt line shape and spectroscopic parameters from the atm line list (Toon, 2014) [6 ]. The same laboratory spectra were used to test absorption coefficients calculated using the qSDV+LM line shape with spectroscopic line parameters from Devi et al. [1, 2 ] for the 2v3 band of CH4 and a Voigt line shape for lines that don't belong to the 2v3 band. The spectral line list for lines that don't belong to the 2v3 band is an amalgamation of multiple spectral line lists. We found that for the P, Q, and R branches of the 2v3 band, the qSDV+LM simulated the laboratory spectra better than the Voigt line shape. The qSDV+LM was also used in the spectral fitting of high-resolution solar absorption spectra from four ground-based remote sensing sites and compared to spectra fitted with a Voigt line shape. The average root mean square (RMS) residual for 131, 124 solar absorption spectra fitted with absorption coefficients calculated using the qSDV+LM for the 2v3 band of CH4 and the new spectral line list for lines for lines that don't belong to the 2v3 band, was reduced in the P, Q, and R branches by 5%, 13%, and 3%, respectively when compared with spectra fitted using a Voigt line shape and the atm line list. We found that the average total column of CH4 retrieved from these 131, 124 spectra, with the qSDV+LM was 1.1±0.3% higher than the retrievals performed using a Voigt and the atm line list. The airmass dependence of the retrieved total columns was found to change depending on the choice of spectral line shape. With the Voigt line shape, we found a minimum in CH4 total columns at a solar zenith angle (SZA) of about 70°. With the qSDV+LM, the retrieved total column of CH4 decreased monotonically as a function of SZA. Graphical abstract: Highlights: Speed dependence and line mixing (qSDV+LM) were used to calculate CH4 absorption coefficients. CH4 laboratory spectra were used to validate absorption coefficients. Spectroscopic line parameters for the 2v3 band were tested using high-resolution solar absorption spectra. Solar absorption spectra are fitted better with the qSDV+LM when compared to the Voigt. The spectral fits and airmass dependence improved at high solar zenith angles with the qSDV+LM.